Comparative Study: Analyzing Translation Technique of Taboo Expressions in Deadpool 2 by Google Play Movie & TV Translator and Subscene.com Translator - Ariani, Kurnia Tri (Universitas Sebelas Maret, 2021)
This research focuses on the translation analysis of taboo expressions in “Deadpool 2” movie. This study aims to find out (i) the type of taboo in the movie and (ii) the techniques employed by two different translators from different platforms to translate taboo expressions. This is a descriptive-qualitative research. The sources of data in this research are the dialogue in movie titled “Deadpool 2” and its Indonesian subtitles produced by 2 different translators, also respondents to assess the translation acceptability whichh in this research called as familiarity. The data in this research are 167 data of taboo expressions found in the said movie and its translations and information from respondents concerning familiarity of the translations. The results of the analysis of the category of taboo expression shows that from 167 data there are eight categories of taboo that are identified in “Deadpool 2”. The categories are sexual references (41%), profane or blasphemous (11%), scatological referents and disgusting object (10%), some animal names (2%), ethnic-racial-gender slurs (1%), insulting references to perceived psychological, physical, or social deviations (7%), ancestral allusions (2%), and offensive slang (25%). The analysis of translation techniques employed by the two translators shows that in total there are eleven translation techniques, namely maintaining with the same lexical items, maintaining with different lexical items, mitigating with the same lexical items, mitigating with different lexical items, generalization, deletion, translating to proper interjection, euphemism, reformulation, substitution and literal translation.